Synthesis and characterization of one-dimensional GaN nanostructures prepared via halide vapor-phase epitaxy - Byeun, Y.-K.; Choi, D.-M.; Han, K.-S.; Choi, S.-C. (Korean Ceramic Society, 2007)
High-quality one-dimensional GaN nanorods and nanowires were synthesized on Ni-coated c-plan sapphire substrate using halide vapor-phase epitaxy (HVPE). Their structure and optical properties were investigated by X-ray diffraction, scanning and transmission electron microscopy, and photoluminescence techniques. Full substrate coverage of densely packed, uniform, straight and aligned one-dimensional GaN nanowires with a diameter of 80nm were grown at 700-900°C. The X-ray diffraction patterns, transmission electron microscopic image, and selective area electron diffraction patterns indicate that the one-dimensional GaN nanostructures are a pure single crystalline and preferentially oriented in the [001] direction. We observed high optical quality of GaN nanowires by photoluminescence analysis.